A MULTI-CRITERIA ASSESSMENT OF READINESS FOR DISRUPTIVE TECHNOLOGY IMPLEMENTATION IN SUPPLY CHAIN MANAGEMENT: A RISK RESPONSE FRAMEWORK PERSPECTIVE - Tramarico, Claudemir Leif [UNESP] (FapUNIFESP (SciELO), 2024)
This paper highlights the challenges and opportunities introduced by disruptive technology for organizations. The convergence of emerging technologies holds the potential to enhance logistics and supply chain decision-making through heightened automation. The paper aims to conduct a multi-criteria assessment of readiness for implementing disruptive technology in supply chain management. The proposed approach employs the multi-criteria decision analysis methodology to assess organizational readiness and technological readiness. The approach suggests a procedure involving an analysis of benefits, opportunities, costs, and risks. It prioritizes and ranks factors associated with both organizational and technological readiness for the implementation of disruptive technology in supply chain management. Additionally, it introduces a supply chain risk response framework to tackle challenges related to readiness. Supply chain management and disruptive technology are expanding fields that provide significant opportunities for exploration. One of these opportunities involves assessing readiness from multiple perspectives, as presented in this paper, contributing to the literature.
Keywords: disruptive technology; readiness; supply chain management; TOPSIS